2020
DOI: 10.1111/cpr.12944
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial for treatment of COVID‐19 patients with pulmonary fibrosis using hESC‐IMRCs

Abstract: Immunity-and-matrix-regulatory cells derived from human embryonic stem cells safely and effectively treat mouse lung injury and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…Currently (December 21, 2020), results from seven single case studies and five small studies (7, 9, 12, 16, and 27 patients, respectively) have been published, where MSCs were employed as therapy on COVID-19 patients ( Feng et al, 2020 ; Liang et al, 2020 ; Meng et al, 2020 ; Scherger et al, 2020 ; Sengupta et al, 2020 ; Shu et al, 2020 ; Soler Rich et al, 2020 ; Tao et al, 2020 ; Yilmaz et al, 2020 ; Zengin et al, 2020 ; Zhang et al, 2020 ). The phase I clinical trial with the 27 patients ( Wu et al, 2020c ) with COVID-19 followed the first case study ( Wu et al, 2020a ) of infusion of MSC-like cells [called human embryonic stem cell-derived immunity- and matrix-regulatory cells ( Wu et al, 2020b )] that show higher immunomodulatory potential than standard adult MSCs. These results, although from few patients, suggest that intravenous infusion of MSCs in COVID-19 patients does not cause severe side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Currently (December 21, 2020), results from seven single case studies and five small studies (7, 9, 12, 16, and 27 patients, respectively) have been published, where MSCs were employed as therapy on COVID-19 patients ( Feng et al, 2020 ; Liang et al, 2020 ; Meng et al, 2020 ; Scherger et al, 2020 ; Sengupta et al, 2020 ; Shu et al, 2020 ; Soler Rich et al, 2020 ; Tao et al, 2020 ; Yilmaz et al, 2020 ; Zengin et al, 2020 ; Zhang et al, 2020 ). The phase I clinical trial with the 27 patients ( Wu et al, 2020c ) with COVID-19 followed the first case study ( Wu et al, 2020a ) of infusion of MSC-like cells [called human embryonic stem cell-derived immunity- and matrix-regulatory cells ( Wu et al, 2020b )] that show higher immunomodulatory potential than standard adult MSCs. These results, although from few patients, suggest that intravenous infusion of MSCs in COVID-19 patients does not cause severe side effects.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 The potential efficacy and safety of MSC treatment have also been evaluated in patients with ARDS. 16 19 Types of stem cell other than MSC, 34 such as human embryonic stem cell-derived immunity- and matrix-regulatory cells (hESC-IMRCs), 35 have also been employed to treat COVID-19 patients (Fig. 1 ).…”
Section: Rationale For Stem-cell Therapiesmentioning
confidence: 99%
“… 41 44 Very recently, Mirakaj et al found that patients who underwent MSC treatment, compared against control patients, experienced significantly lower lung damage (Murray score) upon discharge, had a higher survival rate to discharge, and had better recovery of pulmonary functions. 20 , 45 , 46 Apart from MSCs, Wu et al 35 showed that lung fibrotic lesions were decreased by transfusion of hESC-IMRCs in patients with pulmonary fibrosis.…”
Section: Clinical Trials Of Msc Therapies For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Those therapies may cause concern about safety but many clinical trials has been studying the safeness and efficacy of mesenchymal stem cells therapies. Most recent describes Phase 1 trial for treatment of COVID-19 patients with pulmonary fibrosis using hESC-IMRCs [14] in which none of the treated patients suffered any adverse events or abnormal responses related to cell therapy. This suggest that stem cell therapies has become more and more safe, popular and researchers discover every year new potential fields of treatment with usage of stem cells.…”
Section: Author Detailsmentioning
confidence: 99%